(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2021)
Construction projects are increasingly complex, resulting in complex contract documents. Complex construction can likewise often result in complex disputes, which predominantly arise from the intricacy and magnitude of the work, multiple prime contracting parties, poorly prepared andor executed contract documents, inadequate planning, financial issues, and communication problems. Any one of these factors can derail a project and lead to complicated litigation or arbitration, increased costs, and a breakdown in the parties’ communication and relationship. The current methodology for preventing andor resolving construction conflicts it is not meant to be an exhaustive review of each and every process, but rather to give the reader an overview of the advantages and disadvantages of each process when determining which one is right for a particular situation. India has an ambitious plan to revamp and create railways, inland waterways, ports, highways and smart cities. This paper examines the existing mechanisms of claim settlement and dispute resolution in construction contracts in India and its adequacy including proposed legislative reforms and suggestions. The thesis is divided into two parts, theoretical and practical parts. The theoretical part covers basic alternative methods of dispute resolution at the early and late stages of construction processes and attempts to understand, which method is better to use in each situation.